Integrating Combined First Trimester Screening for Preeclampsia into Routine Ultrasound Examination - Trottmann, Fabienne; Mollet, Anne Elena; Amylidi-Mohr, Sofia; Surbek, Daniel; Raio, Luigi; Mosimann, Beatrice (Geburtshilfe und Frauenheilkunde, 2022)
Introduction The Fetal Medicine Foundation (FMF) London has developed a first trimester screening algorithm for preeclampsia (PE), based on maternal characteristics and past risk factors, mean arterial pressure (MAP), uterine artery pulsatility index (UtA-PI), and placental growth factor (PlGF). The aim of this study was to determine the feasibility of integrating PE screening into routine practice.Material and Methods All pregnancies with a fetal crown-rump length of 45 – 84 mm presenting to our ultrasound department between January 2014 and September 2020 were included in this analysis. Screening for PE was offered to singleton pregnancies only. The number of screening tests performed in the eligible population was assessed and the reasons for missed screenings identified with the help of the electronic clinical database. SPSS Statistics 25 and GraphPad version 8.0 for Windows were used for statistical analysis.Results 6535 pregnancies were included, 4510 (69.0%) of which were screened for PE. The percentage of patients being offered PE screening increased over the years from 63.1 to 96.7% (rs = 0.96; p = 0.003), while the rate of screenings performed in eligible patients remained stable at a median [range] of 86.2% [78.0 – 91.8%] (p = ns). 2025 (31.0%) pregnancies were not screened for PE, 1306 (64.5%) because they were not eligible for screening. 145 (2.2%) women explicitly declined PE screening; their background risk was lower than that of women who accepted screening.Conclusion Our study shows that integration of PE screening into the routine first trimester ultrasound scan is feasible and widely accepted by pregnant women and health care providers.
Keywords: obstetrics; sonography; pregnancy; preeclampsia; epidemiology